2013
DOI: 10.1155/2013/857929
|View full text |Cite
|
Sign up to set email alerts
|

Active Constituents fromLiriope platyphyllaRoot against Cancer GrowthIn Vitro

Abstract: Liriope spicata is a well-known herb in traditional Chinese medicine, and its root has been clinically demonstrated to be effective in the treatment of metabolic and neural disorders. The constituents isolated from Liriope have also recently been shown to possess anticancer activity, although the mechanism of which remains largely unknown. Here, we illustrate the anticancer activity of LPRP-9, one of the active fractions we fractionated from the Liriope platyphylla root part (LPRP) extract. Treatment with LPRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Several studies on the direct effect against UBC have suggested that a homogeneous polysaccharide from Panax ginseng displayed potent antiproliferative and antimetastatic activities in human bladder T24 cells, and Rg3 ginsenoside inhibited the proliferation of EJ (human bladder transitional cell carcinoma cells) by inducing apoptosis [ 21 , 22 ]. Additionally, treatment with Liriope platyphylla significantly inhibited proliferation of MCF-7 (breast carcinoma cells) and Huh-7 (hepatic carcinoma cells) by inducing apoptosis and autophagy pathways [ 23 ]. DT-13, a saponin monomer from Liriope platyphylla , showed antiangiogenic effects mediated by reductions in vascular endothelial growth factor (VEGF), C-C chemokine receptor type 5 (CCR5), and hypoxia-inducible factor 1 α (HIF-1 α ) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the direct effect against UBC have suggested that a homogeneous polysaccharide from Panax ginseng displayed potent antiproliferative and antimetastatic activities in human bladder T24 cells, and Rg3 ginsenoside inhibited the proliferation of EJ (human bladder transitional cell carcinoma cells) by inducing apoptosis [ 21 , 22 ]. Additionally, treatment with Liriope platyphylla significantly inhibited proliferation of MCF-7 (breast carcinoma cells) and Huh-7 (hepatic carcinoma cells) by inducing apoptosis and autophagy pathways [ 23 ]. DT-13, a saponin monomer from Liriope platyphylla , showed antiangiogenic effects mediated by reductions in vascular endothelial growth factor (VEGF), C-C chemokine receptor type 5 (CCR5), and hypoxia-inducible factor 1 α (HIF-1 α ) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the culture supernatant had been removed for nitrite determination, we used the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) solution to assess the cell viability as previously described [27]. In brief, 0.5 mg/mL of MTT in DMEM was added to each well of cells and incubated in cell culture condition for 3 h. Then, the supernatant was removed from each well by suction, and 100 μL of DMSO was added to dissolve the formazan crystals.…”
Section: Methodsmentioning
confidence: 99%
“…It also activates the MAPK pathways. (-)-Liriopein B is capable of inhibiting Akt phosphorylation at low concentration [66]. The nontoxic doses are able to inhibit AKT activation in both luminal-like MCF-7 and basal-like MDA-MB231 breast cancer cells.…”
Section: Anti-cancer Activitymentioning
confidence: 97%